Differences between solution and membrane forms of chitosan on the ın vitro activity of fibroblasts - (:unkn) unknown (My University, 2015)
0

Background: Chitosan, a linear polysaccharide, has been recently used in biomedical applications. In vitro studies have demonstrated its effect on cellular growth and its stimulatory action on cellular layer formation. Aims: The present study aims to compare the prolif- erative effects of chitosan in two forms, membranous and solution forms, on Swiss 3T3 mouse embryonic fibroblasts. Study Design: In vitro study. Methods: Three experimental groups were formed: cells were cultured in a normal medium without chitosan (Control Group); cells were cultured ei- ther in a medium containing 2.0% chitosan in mem- branous form (Membrane Group) or chitosan solu- tion at a concentration of 2.0% (Solution Group). Two different methods were used in the experi- ments: cells cultured on the medium containing chitosan in solution or membranous forms (method 1); and chitosan solution or membranous forms were added into the medium containing previ- ously cultured cells (method 2). Results: Scanning electron microscopic investigations of the experimental groups revealed cells with well- defined cellular projections, intact cellular membranes and tight intercellular junctions. They were especially prominent in the membrane group of method 1 and in the membrane and solution groups of method 2. Mouse monoclonal anti-collagen 1 primary antibody was used to indicate collagen synthesis. Prominent collagen synthesis was detected in the membrane groups on the 10th day of culture for both methods. Bromodeoxyuridine (BrdU) and MTT assays were performed in order to assess cellular proliferation and viability, respectively. BrdU labelling tests indicated a higher proliferation index in the membrane group of method 1 on the 5th and 10th days. For the second method, the membranous form on the 10th day and solution form on the 5th day were the most effective groups in terms of cellular proliferation. MTT results reflected a high cellular viability in method 1 on the 5th day of treatment with the membranous form, whereas cellular viability was highest in the solution form of method 2 on the 5th day. Conclusion: The membranous form of chitosan induced a significant proliferative effect and increased the ratio of cell-to-cell junctions of Swiss 3T3 mouse embryonic fibroblasts. Conveniently, the solution form also resulted in enhanced cell proliferation and viability compared to the control group. As the solution foris easy to prepare and apply to cells compared to the membrane form, the application of Chitosan directly to media appears to be a convenient alternative for tissue engineering approaches.
Keywords: Cerrahi